2017
DOI: 10.1016/j.wasman.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment and life cycle costs for pre-disaster waste management systems

Abstract: This study develops a method of environmental and economic evaluation of an integrated disaster waste management system that considers the spatial scale of removal, transport, and treatment of disaster waste. A case study was conducted on combustibles, which is a type of disaster waste derived from dwellings, in Mie Prefecture, Japan. First, we calculated the quantity and the spatial distribution of disaster waste derived from dwellings and tsunami debris produced as a result of a large-scale earthquake. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…Disaster waste closely depend upon the type of disaster (Brown et al, 2011a). After careful scanning, the authors of this review found that a few authors discussed waste management in various disaster contexts (Tabata et al, 2017;Wakabayashi et al, 2017;Asari et al, 2013;Koyama et al, 2016;Pramudita and Taniguchi, 2014). Therefore, the total number of papers reviewed by disaster type was 89.…”
Section: Disaster Type Mentioned In the Selected Papersmentioning
confidence: 99%
“…Disaster waste closely depend upon the type of disaster (Brown et al, 2011a). After careful scanning, the authors of this review found that a few authors discussed waste management in various disaster contexts (Tabata et al, 2017;Wakabayashi et al, 2017;Asari et al, 2013;Koyama et al, 2016;Pramudita and Taniguchi, 2014). Therefore, the total number of papers reviewed by disaster type was 89.…”
Section: Disaster Type Mentioned In the Selected Papersmentioning
confidence: 99%
“…The literature research highlighted the possibility to develop studies for the prediction of both the environmental and the economic impact of a disaster waste management, also considering possible innovative approaches for the scraps exploitation, mainly in Japanese areas (Portugal‐Pereira & Lee, ; Tabata, Wakabayashi, Tsai, & Saeki, ; Wakabayashi, Peii, Tabata, & Saeki, ). The papers focused on specific critical impact categories and they included defined areas, with their related peculiarities.…”
Section: Discussionmentioning
confidence: 99%
“…A similar cash for work model was adopted in the demolition and removal of debris from damaged buildings in Haiti after the earthquake in 2010 (United Nations Development Programme, 2013). Case studies on pre-disaster management by local governments are essential for different types of disasters, and their scales and maximum damage levels can provide information about the debris that could be generated, thereby enabling debris removal plans, open spaces required for temporary storage, transportation networks, and management options to be planned in advance (Tabata et al, 2017;Wakabayashi et al, 2017). The debris management system framework suggested by Kim et al (2018) and Srour et al (2013) can enable decision-makers to determine the necessary budget and time for debris removal in a timely manner by incorporating past debris removal data into the proposed framework and comparing the difference between the actual costs and those estimated by the system to enhance the robustness of its evaluation of an existing system under different disaster scenarios.…”
Section: Dismantling Of Collapsed Houses Using Public Financesmentioning
confidence: 99%